2019
DOI: 10.1088/2053-1583/ab01eb
|View full text |Cite
|
Sign up to set email alerts
|

Perseverance of direct bandgap in multilayer 2D PbI 2 under an experimental strain up to 7.69%

Abstract: The two-dimensional (2D) materials are naturally suitable for various flexible 2D optoelectronic devices, in which the direct band gap perseverance is crucial because the flexibility deformations often cause a bandgap transition and thus break performance of the devices. Most of 2D transition metal dichalcogenides (TMDs) materials such as monolayer MoS 2 , WS 2 and MoSe 2 have been thought to be not suitable for flexible optoelectronic devices due to their direct-to-indirect bandgap transition even under a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…The high energy emission peak at 2.43 eV refers to the free excitonic recombination. On the basis of PL and absorption measurements, we demonstrate that our PbI2 crystal is a direct semiconductor [21]. For the purpose of studying the temperature dependence of band gap energies, we performed the temperature-dependent transmittance measurements in the temperature range between 20 and 300 K. Figure 4a shows the absorption spectra measured at different temperatures, and the inset figure shows the comparison of reflectance and absorption spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high energy emission peak at 2.43 eV refers to the free excitonic recombination. On the basis of PL and absorption measurements, we demonstrate that our PbI2 crystal is a direct semiconductor [21]. For the purpose of studying the temperature dependence of band gap energies, we performed the temperature-dependent transmittance measurements in the temperature range between 20 and 300 K. Figure 4a shows the absorption spectra measured at different temperatures, and the inset figure shows the comparison of reflectance and absorption spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The high energy emission peak at 2.43 eV refers to the free excitonic recombination. On the basis of PL and absorption measurements, we demonstrate that our PbI 2 crystal is a direct semiconductor [21]. In order to identify the band gap energy, we performed the transmittance and photoluminescence (PL) measurements at 300 K. At sub-band gap photon energies, a semiconductor is basically transparent, meaning that no photon absorption happens in this energy range and most of the incident light can pass through the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, these experimental results are good agreement to theoretical models. Recently, Du et al [155] used the same method and found that the 2D PbI 2 multilayer maintains a direct band gap nature under a large experimental strain up to 7.69%. The strained 2D PbI 2 offers reference for potential optoelectronic device applications.…”
Section: Applying Strain By Creating Wrinkles In 2d Semiconductorsmentioning
confidence: 99%
“…[17,18] Therefore, PbI 2 could become a good supplement for the existing TMDs and other 2D optoelectronic materials. In addition, PbI 2 has a wider bandgap, higher light absorption coefficient, and better perseverance of direct bandgap than TMDs materials, [19][20][21][22][23] and has potential applications in nuclear radiation detectors, [24] low-threshold lasers, [25] and high-efficiency photodetectors. [26] However, there is a fly in the ointment, that is, the stability, especially photostability, of PbI 2 is inferior to that of TMDs materials.…”
Section: Introductionmentioning
confidence: 99%